LiK B1Π potential: combining short and long-range data - Botsi, S. (2020)
We present spectroscopic measurements of the long range states of the 6Li40K molecule near its Li(42S1/2) + K(42P3/2) asymptote which in combination with existing data in the short range lead to the full characterization of the B1Π potential with high spectroscopic resolution. This survey was conducted in the context of identifying a suitable pathway for the efficient two-photon transfer to the absolute ro-vibronic ground state of 6Li40K heteronuclear dimers.